Antagonistic species interaction drives selection for sex in a predator–prey system. (21st June 2020) - Koch, Hanna R.; Wagner, Sophia; Becks, Lutz
Abstract: The evolutionary maintenance of sexual reproduction has long challenged biologists as the majority of species reproduce sexually despite inherent costs. Providing a general explanation for the evolutionary success of sex has thus proven difficult and resulted in numerous hypotheses. A leading hypothesis suggests that antagonistic species interaction can generate conditions selecting for increased sex due to the production of rare or novel genotypes that are beneficial for rapid adaptation to recurrent environmental change brought on by antagonism. To test this ecology‐based hypothesis, we conducted experimental evolution in a predator (rotifer)–prey (algal) system by using continuous cultures to track predator–prey dynamics and in situ rates of sex in the prey over time and within replicated experimental populations. Overall, we found that predator‐mediated fluctuating selection for competitive versus defended prey resulted in higher rates of genetic mixing in the prey. More specifically, our results showed that fluctuating population sizes of predator and prey, coupled with a trade‐off in the prey, drove the sort of recurrent environmental change that could provide a benefit to sex in the prey, despite inherent costs. We end with a discussion of potential population genetic mechanisms underlying increased selection for sex in this system, based on our application of a general theoretical framework for measuring the effects of sex over time, and interpreting how these effects can lead to inferences about the conditions selecting for or against sexual reproduction in a system with antagonistic species interaction. Abstract : Can antagonistic species interaction, without coevolutionary change, select for sexual reproduction? Using experimental evolution in a predator‐prey system, fitness assays, and a general theoretical framework for the evolution of sex, we found evidence supporting the hypothesis that fluctuating population sizes of predatory and prey, coupled with a trade‐off in the prey, can drive the sort of recurrent environmental change providing a benefit to sex in the prey, despite inherent costs. Sex was not observed in prey populations without predation.